Representing plant diversity in land models: An evolutionary approach to make "Functional Types" more functional. (26th January 2022) - Anderegg, Leander D. L.; Griffith, Daniel M.; Cavender‐Bares, Jeannine; Riley, William J.; Berry, Joseph A.; Dawson, Todd E.; Still, Christopher J.
Abstract: Plants are critical mediators of terrestrial mass and energy fluxes, and their structural and functional traits have profound impacts on local and global climate, biogeochemistry, biodiversity, and hydrology. Yet, Earth System Models (ESMs), our most powerful tools for predicting the effects of humans on the coupled biosphere–atmosphere system, simplify the incredible diversity of land plants into a handful of coarse categories of "Plant Functional Types" (PFTs) that often fail to capture ecological dynamics such as biome distributions. The inclusion of more realistic functional diversity is a recognized goal for ESMs, yet there is currently no consistent, widely accepted way to add diversity to models, that is, to determine what new PFTs to add and with what data to constrain their parameters. We review approaches to representing plant diversity in ESMs and draw on recent ecological and evolutionary findings to present an evolution‐based functional type approach for further disaggregating functional diversity. Specifically, the prevalence of niche conservatism, or the tendency of closely related taxa to retain similar ecological and functional attributes through evolutionary time, reveals that evolutionary relatedness is a powerful framework for summarizing functional similarities and differences among plant types. We advocate that Plant Functional Types based on dominant evolutionary lineages ("Lineage Functional Types") will provide an ecologically defensible, tractable, and scalable framework for representing plant diversity in next‐generation ESMs, with the potential to improve parameterization, process representation, and model benchmarking. We highlight how the importance of evolutionary history for plant function can unify the work of disparate fields to improve predictive modeling of the Earth system. Abstract : Representing the enormous diversity of land plants in Earth System models remains extremely challenging. Because ecological and physiological functions tend to be conserved in closely related species through evolutionary time, evolutionary relatedness can help summarize plant functional diversity into a tractable number of "Lineage Functional Types" that represent the most functionally distinct and logically consistent vegetation groupings on the land surface. This evolutionary approach holds the potential to improve model parameterization, identify areas for process development, and open up new methods of model benchmarking (e.g., with remote sensing data) for vegetation modeling applications across spatial scales.